May Her Likes Be Multiplied - Nancy L. Stockdale (International Institute of Islamic Thought, 2002)
Marilyn Booth's remarkable study blends literary criticism with historical research to better understand the construction of modem Egyptian womanhood. Booth analyzes hundreds of women's biographies that were written in the late nineteenth and early twentieth centuries and published in the popular women's press. She situates this activity within the context of Egypt's nationalist struggle and burgeoning feminist movement at a time of foreign economic, military, and cultural domination. With the publication of biographies of women as diverse as the Prophet's wives, Jeanne d'Arc, Hatshepsut, Jane Austin, and Safiyya Zaghlul, Booth uncovers the diversi ty of the Egyptian women's press in its scope and vision of what Egypt should expect of its women. Booth complicates our understandings of women's participation in the public sphere by illuminating the ethnic and religious diversity of the Egyptian women's press. She also delves deeply into the class issues motivating the construction of the ideal Egyptian woman as a selfless member of her family - both nuclear and national - conforming her domestic sphere to the mold of communal, nationalist needs. Revealing women authors as both shaping and being shaped by contemporary ideas of successful femininity, Booth's study is perhaps the most potent analysis of Egyptian feminism published in quite some time. It is an indispensable guide to a literature steeped in the Arabic literary past as well as modem Egyptian society. In a complex prologue, Booth argues that any examination of authorship can only vaguely determine how audiences react to published texts. Thus, although she sets out to analyze the messages inherent in women's biographies, she cannot relay the manner in which the women's press was received by its audience. Her book is an analysis of prescription through example, but only can hint at the resulting impact. Booth focuses on how these biographies became part of a larger social project to define women as national symbols situating the nation as the ultimate community, all the while maintaining patriarchal constructs in the home and other social spheres. She declares the biographies she examines to be ultimately "feminist," for, although they often maintain crucial elements of the status ...